Diferentes terapias na osteoartrite induzida por papaína em joelhos de ratos - Rosseto, Laryssa Petrocini [UNESP] (2016)
Due to increasing life expectancy of animals and the growing number of people, osteoarthritis (OA), also known as arthrosis, appears as one of the most important diseases in veterinary and human medicine. Several treatments are use and proposed, but there is no consensus about the best therapy. This study aimed to investigate and compare the efficacy of Low-level laser therapy and therapeutic ultrasound in conjunction with platelet-rich plasma (PRP) in the treatment of osteoarthritis induced in rats’ knees. Randomly were used 72 mice divided into nine groups of eight animals: Control Group (CG), group saline (GCF), Group osteoarthritis 21 days (GOA21), Group osteoarthritis 42 days (GOA42), Group osteoarthritis and Laser (GOALa), Group osteoarthritis and therapeutic Ultrasound (GOAUS), osteoarthritis and PRP Group (GOAPrp), osteoarthritis Group, PRP and Laser (GOAPrpLa) and Group osteoarthritis, PRP and therapeutic ultrasound (GOAPrpUS). It was performed intra-articular infiltration of papain and cysteine 0.03M 4% and 21 days after the induction started three weeks treatment with laser, ultrasound and / or PRP. Evaluations were performed perimeter, thermographic, macro and microscopic. A significant interaction between the groups with respect to time to the perimeter and thermographic ratings, proving that thermography was effective to evaluate the behavior of articular inflammation. Macroscopic changes were observe in the articular cartilage in any animal, a fact confirmed in the histopathological evaluation, which showed up distension and inflammation of the joint capsule, indicating the presence of synovitis. Based on these results it was conclude that the application of a single dose of 4% papain intraarticular is not sufficient to induce osteoarthritis in the knees of mice, but synovitis. In addition, the best results to inflammation of the synovium were using PRP alone or in combination with a laser.